East meets West: current issues relevant to integrating Chinese medicine - Wong Emily; Gaster Barak; Lee Sum (BMC, 2012)
Abstract This article describes the challenges that integration of Chinese medicine (CM) and biomedicine are likely to bring for improving safety, research, education, and cross-disciplinary communication. Potential strategies to meet these challenges are suggested, including the use of accessible language for the Western biomedical community, and further development of whole-system randomized controlled trials that support individualized treatment approaches.